Gross National Happiness in the Context of Networked Learning - Zander, Pär-Ola; Choeda; Penjor, Tandin; Kinley (Proceedings of the International Conference on Networked Learning, 2016)
Gross National Happiness (GNH) has attained considerable interest as an alternative to the prevalent profit-driven global economy. It is a general prescriptive theory of development, putting happiness at the center rather than economic growth. This theory is originating from Bhutan, but can be applied in any society or area of society; in business, in government, etc. Education is seen as instrumental in implementing a GNH society. With the intent to infuse GNH in the Bhutanese education system all school principals, district education officers, heads of the Royal University of Bhutan (RUB) colleges, and selected academics from RUB colleges were trained to infuse GNH in the country’s education system in 2010. How to implement it is a exhilarating challenge, where some educational efforts will be addressed without technology playing a key role, whereas other will utilize networked technologies. In this paper, we theorize outline what GNH may mean in a networked learning context, and as concretization, how networked learning can support infusion of GNH in education. The unfolding of the possibilities are based on conceptual analysis and existing literature, and illustrated by empirical data from the country where GNH is supposedly most devotedly pursued in Bhutan. For example all developmental activities plans and proposals are screened through GNH lens administered by the GNH Commission before approval for implementation by the agencies and organizations. We structure our finding through three relevant areas of ICT support of GNH; Outcome, message and medium. GNH as outcome concerns learning outcomes, GNH as message is when GNH is included in learning materials and curricula, and GNH as medium regards the learning environment designed according to a certain set of principles. While all areas are somewhat evocative, we find ICT-support for the medium the most promising for further research in networked learning. GNH consists of a number of domains, which can be seen as describing an environment, such as cultural diversity, conscious time use, and organic learning materials and buildings. This can be built into online and blended learning environments, and be followed by investigations on what kind of learning that unfolds in them. By exploring the three areas, we sketch a possible research program of GNH. We find GNH a promising agenda that deserves further design-based inquiry.